DAMPAK DAN ANALISIS STRATEGI KOMUNIKASI DALAM PEMULIHAN KASUS KERUSUHAN 98 PADA ETNIS TIONGHOA - Jiovanie Maria Margaret Munthe; Sayyidah Rachmawati (ADISAM PUBLISHER, 2025)
After Indonesia gained independence, the country experienced numerous conflicts that generated controversy. The year 1998 remains one of the most unforgettable periods due to widespread riots that resulted in many casualties and targeted attacks against the ethnic Chinese community. The May 1998 riots constituted a bloody moment for Chinese Indonesians. This study aims to collect, analyze, and process information regarding the 1998 riots and their impact on the ethnic Chinese community, as well as to examine the communication strategies employed during the recovery phase. The method used in this study is a literature-based approach (library research). Data collection was conducted by reviewing and exploring various journals, books, and documents both printed and electronic as well as other data sources and information considered relevant to the study